(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The bending strength of porcelain body has been experimentally studied because of its economic importance in ceramic industry. The maximum bending strength is obtained in the < 44Î¼ particle sized quartz containing porcelain at 1300Â°C. The distribution of closed pores, their geometric shapes and possible link with each other control the bending strength of the ceramic body. The presence of unmelted fine quartz grains in the ceramic body also increases the bending strength. It has been found that the bending strength increases with increasing bulk density of the ceramic bodies and the firing temperature up to 1300Â°C, but at temperature above 1300Â°C, the bending strength decreases due to bloating of isolated pores and the disappearance of quartz, which are also associated with a decrease in bulk density. The purpose of this study is to investigate on the differential changes of bending strength of porcelain bodies upon using quartz of various grain sizes at different firing temperatures. Key Words: Particle size, Quartz, Bending strength, Firing temperature and bulk density. Â Â doi: 10.3329/bjsir.v43i4.2244 Bangladesh J. Sci. Ind. Res. 43(4), 537-544, 2008